Medikamentöse Therapie der Endometriose - Burghaus, Stefanie; Beckmann, Matthias (Die Gynäkologie, 2024)
In Germany, the progestin dienogest, the gonadotropin-releasing hormone (GnRH) agonists leuprorelin, goserelin, and nafarelin, and, since November 2023, the GnRH antagonist relugolix combination therapy (relugolix-CT) have been approved for hormonal drug therapy of endometriosis. In the first-line treatment of endometriosis, oral progestin preparations have proven effective. In second-line treatment, oral estrogen–progestin combination preparations, alternative forms of progestin administration such as the hormone coil, and GnRH agonists have proven effective. GnRH agonists have low compliance due to their range of side effects and their administration should be supplemented by add-back therapy. Another option is now treatment with the GnRH antagonist relugolix-CT following previous pharmaco- or surgical therapy. Non-hormonal drug therapy can be carried out symptomatically with analgesics such as nonsteroidal anti-inflammatory drugs.
CRIS-Team Scopus Importer:2024-02-09
Keywords: Dienogest; Estrogens; GnRH analoga; Progestins; Relugolix